The Known and Unknown Sea - Alan Bilton (Cillian Press, 2014)
NovelThis haunting and comic fable from the author of The Sleepwalkers' Ball is a beautiful and heartbreaking journey through memory, loss and imagination.Rumour and suspicion engulf an eerily fog-bound town as its residents begin to receive tickets promising passage across the mist-shrouded bay to the mysterious 'other side'. For Alex and his family, this seems like the beginning of a great adventure, but as reports of a shadowy, half-glimpsed ship start to circulate, so too does the gossip and anxious speculation.Bilton has created an alternate universe, vividly detailed but utterly ambiguous, absurd and bewildering, a dream that lingers in the mind long after the last page is turned.Dreamlike and immersive, The Known and Unknown Sea is a pantomime nightmare, surreal, terrifying and hilarious, full of masks and metamorphoses. It's a world seen through the eyes of children, magical, kaleidoscopic and incomprehensible, beautifully characterised: the fierce Bethan, little Hwyl with his rag-doll indestructibility, the bearded ogre of The Ship's Doctor. The book is a darkness lit by flashes of blinding light and sudden, bewildering changes of scene, an infinitely spiralled, inescapable world that echoes with strange voices: Freud and Dylan Thomas, Dante, Kafka and Günter Grass.